Gambaran Kadar D-Dimer pada Pasien Stroke Iskemik - Ticoalu, Micha M. C.; Wowor, Mayer F.; Rambert, Glady I. (Universitas Sam Ratulangi, 2025)
Abstract: The primary cause of ischemic stroke is atherosclerosis affecting major arteries in the neck and head. D-dimer is linked to ischemic stroke, as it is the end product of fibrin breakdown by plasmin through the fibrinolytic process. This study aimed to assess D-dimer levels in ischemic stroke patients at Prof. Dr. R. D. Kandou Hospital, Manado. This was a descriptive and retrospective study using the total sampling method. The results showed that there were 15 patients meeting the inclusion criteria for ischemic stroke patients consisting of nine male patients and six female patients. The majority of patients were in the age group of 60-79 years (53.3%), followed by age group 40-59 years (33.3%), and age group 80-99 years as well as 20-39 years (each of 6.67%). All patients with ischemic stroke had increased D-dimer level. In conclusion, the majority of patients with ischemic stroke are males, aged over forty, and have elevated D-dimer level. Keywords: D-Dimer; ischemic stroke Abstrak: Penyebab utama stroke iskemik ialah aterosklerosis yang mengenai arteri besar pada leher dan kepala. D-dimer memiliki hubungan dengan stroke iskemik oleh karena merupakan produk akhir pemecahan fibrin oleh plasmin melalui proses fibrinolitik. Penelitian ini bertujuan untuk mendapatkan gambaran kadar D-dimer pada pasien stroke iskemik di RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah deskriptif retrospektif menggunakan data rekam medis pasien stroke iskemik di RSUP Prof. Dr. R. D. Kandou Manado dengan metode total sampling. Hasil penelitian mendapatkan 15 pasien stroke yang memenuhi kriteria inklusi dan eksklusi, terdiri dari sembilan laki-laki dan enam perempuan. Pasien terbanyak pada kelompok usia 60-79 tahun (53,3%), diikuti oleh kelompok usia 40-59 tahun (33,3%), serta kelompok usia 80-99 tahun dan 20-39 tahun (masing-masing 6,67%). Pada seluruh pasien stroke iskemik didapatkan peningkatan kadar D-dimer. Simpulan penelitian ini ialah majoritas pasien stroke iskemik berjenis kelamin laki-laki, usia di atas 40 tahun, dengan peningkatan kadar D-dimer. Kata kunci: D-Dimer; stroke iskemik